2017
DOI: 10.1016/j.arth.2016.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Femoral Component Initial Stability and Cortical Strain in a Reduced Stem-Length Design

Abstract: Our findings demonstrate that within this fit-and-fill stem design, reduction in stem length improved proximal cortical strain distribution and maintained axial and torsional stability on par with other stem designs in a composite femur model. Short-stemmed implants may accommodate less invasive surgical techniques while facilitating more physiological femoral loading without sacrificing primary implant stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 44 publications
3
25
0
2
Order By: Relevance
“…The clear distal load transfer after the implantation of both short stems demonstrated in this study is congruent with previous studies, which have found a similar distally shifting load distribution pattern as a result of implant insertion (24,61,62). Despite the fact that short stem femoral implants have displayed a better biomechanical behavior preserving a stain distribution closer to the intact bone according to previous studies (24,28,42,43,(63)(64)(65), the implantation of a stiffer material absorbs the load and transfers it distally, leaving the proximal region of the calcar somewhat stress-shielded. The data presented here demonstrate that strain shielding and proximal unloading of the femur occurred even when using short-stem implants.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The clear distal load transfer after the implantation of both short stems demonstrated in this study is congruent with previous studies, which have found a similar distally shifting load distribution pattern as a result of implant insertion (24,61,62). Despite the fact that short stem femoral implants have displayed a better biomechanical behavior preserving a stain distribution closer to the intact bone according to previous studies (24,28,42,43,(63)(64)(65), the implantation of a stiffer material absorbs the load and transfers it distally, leaving the proximal region of the calcar somewhat stress-shielded. The data presented here demonstrate that strain shielding and proximal unloading of the femur occurred even when using short-stem implants.…”
Section: Discussionsupporting
confidence: 92%
“…Digital Image Correlation is an optical fulleld technique that allows noncontact, three-dimensional deformation measurements of objects subjected to external loads. To date, DIC has been used in many applications in biomechanics, such as a measurement tool of strains on bone surface with or without validation of nite element corresponding models (24,31,(52)(53)(54)(55)(56)(57)(58)(59) and also to evaluate relative micromotion between the implant and the surrounding bone (24,60). In this study, we employed the three-dimensional DIC measurement technique to nd the differences in strain patterns generated in composite femurs implanted with two different design femoral prostheses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,15,28 Conversely, the unnatural biomechanical loading and stress-shielding that can occur with neck-sacrificing implants has been associated with increased femoral cortical strain and thigh pain. 4,14,15 Ultimately these factors could cause a patient to perceive a better outcome from their procedure, and may account for better pain HOOS subscores in the NPS cohort in comparison to that receiving the necksacrificing implant. Second, it is widely held that increased femoral offset results in an improved moment arm, abductor strength, gait, and range of motion, leading to better PROs.…”
Section: Discussionmentioning
confidence: 99%
“…4 The concept of neck-preserving stems was introduced by Freeman, Townley, Whiteside, and Pipino to improve biological and mechanical characteristics of femoral stems, and there are observed advantages regarding the effects of preservation of femoral neck bone on preservation of the proximal anatomy and anteversion of the femur, [10][11][12][13] and favorable physiological loading. 10,14,15 Comparison between intact, healthy femoral loading, and NPS stem implants and neck-sacrificing implants loading showed that NPS stem implants produce similar femoral loading patterns to natural distribution, particularly in proximal areas (►Fig. 1).…”
mentioning
confidence: 99%